Can agriculture reach net zero emissions by 2050? - Verchot, Louis V. (2022)
Significant GHG emissions reductions in agriculture are achievable through reducing emission intensity of production, but population growth and dietary changes may offset absolute emissions reductions. Emission reductions consistent with 2030 targets are achievable in many countries; attaining the 2050 targets will require innovation and systems transformation. Net zero agriculture cannot be achieved without sinks. Governance, economics, and sociocultural factors are the keys to food system transformations.